A taxonomic revision of the Southern South American species of the genus Fannia Robineau-Desvoidy (Diptera: Fanniidae) - Dominguez, Martha Cecilia (Papéis Avulsos de Zoologia, 2007)
The Southern South American species of the genus Fannia Robineau-Desvoidy are revised. Twenty five valid species are recognized for the region in the present study: Fannia albitarsis Stein, Fannia anthracina (Walker), Fannia bigoti Stein, Fannia canicularis (Linnaeus), Fannia confusa Pont & Carvalho, Fannia coxata Shannon & Del Ponte, Fannia femoralis (Stein), Fannia flavicornis Stein, Fannia flavipalpis Stein, Fannia fusconotata (Rondani), Fannia heydenii (Wiedemann), Fannia hirtifemur (Stein), Fannia incisurata (Zetterstedt), Fannia petrocchiae Shannon & Del Ponte, Fannia punctiventris Malloch, Fannia pusilla (Bigot), Fannia pusio (Wiedemann), Fannia scalaris (Fabricius), Fannia schnusei Stein, Fannia setosa (Bigot), Fannia tucumanensis Albuquerque, Fannia tumidifemur Stein and three new species from Argentina are described: two from the province of San Luis (Fannia roigi sp. nov. and Fannia hermani sp. nov.) and one from the province of Mendoza (Fannia losgateados sp. nov.). The unknown male of Fannia fusconotata is described for the first time. The Neotropical Fannia euchaetophora Carvalho is synonymized with Fannia flavicornis Stein. Redescriptions are provided for all known species and genitalic illustrations given for both sexes. Keys for each sex are given, and knowledge on the geographical distribution of all species is updated and summarized.